Fundamental Study of Simple Gas Adsorption and Adsorption-Induced Deformation in Carbonaceous Materials - Diao, Rui (Curtin University, 2017)
This thesis has presented a fundamental study of simple gas adsorption and adsorption-induced deformation in carbonaceous materials including both graphite and porous carbon. Monte Carlo simulation was conducted to obtain the behaviours of adsorption and adsorption-induced solid deformation that are comparable to experimental studies including the adsorption isotherm, the strain isotherm and the isosteric heat, as well as the relevant microscopic properties that facilitate the understanding of underlying mechanisms.